Praktik Pembuatan Kompos Di SDN 026 Muara Badak - Ga, Stanislaus Skotska Yosafat; Muliati (ANDIL Mulawarman Journal of Community Engagement, 2025)
The composting practice at SDN 026 Muara Badak aims to provide students with practical knowledge about the composting process as well as to train skills such as selecting materials, cutting, mixing, and using EM4 bioactivators to accelerate decomposition. Before the practice began, students received materials covering the definition of compost, its benefits for greening, and the steps in the manufacturing process. This activity was carried out on August 6, 2024, attended by students in grades IV to VI with high enthusiasm, even though the weather was less than supportive. The students were actively involved in every stage, from preparing materials to mixing and packaging. As a result, this activity succeeded in increasing students' awareness of the importance of managing organic waste and how waste can be turned into useful compost